2017
DOI: 10.1111/trf.14270
|View full text |Cite
|
Sign up to set email alerts
|

Supernatant reduction of stored gamma‐irradiated red blood cells minimizes potentially harmful substances present in transfusion aliquots for neonates

Abstract: BACKGROUND In neonate transfusion, the use of a dedicated red blood cell (RBC) unit decreases donor exposure. A separate safety measure involves gamma irradiation of the RBCs to abrogate the possibility of transfusion‐associated graft‐versus‐host disease. However, in combination, storage of gamma‐irradiated RBCs leads to accumulation of potentially harmful substances in the supernatant. STUDY DESIGN AND METHODS For this study, RBCs were pooled and split into three study arms. Centrifugation or gravity was used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 34 publications
1
4
0
1
Order By: Relevance
“…In agreement with earlier studies, we also found that RBC supernatants possess barrier-disruptive properties (38,46,50,52,56,67). Surprisingly, supernatants from fresh RBCs or old RBCs had same degree of deleterious effects on ECs with that of old RBCs, suggesting that these harmful substances are present in RBC from the beginning, opposing the existing theory that they accumulate during storage.…”
Section: Discussionsupporting
confidence: 90%
“…In agreement with earlier studies, we also found that RBC supernatants possess barrier-disruptive properties (38,46,50,52,56,67). Surprisingly, supernatants from fresh RBCs or old RBCs had same degree of deleterious effects on ECs with that of old RBCs, suggesting that these harmful substances are present in RBC from the beginning, opposing the existing theory that they accumulate during storage.…”
Section: Discussionsupporting
confidence: 90%
“…This conjecture is supported by higher hemolysis and free Hb concentration in the centrifuged sample, and a slightly higher EI at high shear, which is related to the maximal extensibility of RBCs and therefore would increase most if the number of spherical cells is reduced (Table ). The difference in the effect of different types of washing on properties of stored RBCs is intriguing, and should warrant further careful investigation, because of the potential risks associated with transfusion of poorly‐preserved, fragile RBCs to susceptible patients …”
Section: Discussionmentioning
confidence: 99%
“…Supernatant preparation and measurement of variables including free Hb (fHb), potassium ion and RBC-derived microvesicles (RMVs) levels were performed as previously reported. 15 Hemolysis % was calculated according to the following equation: hemolysis % = fHb  (100 À Hct)/Hb t . Lactate dehydrogenase (LDH) concentrations were measured using a colorimetric LDH assay kit (ab 102526, Abcam).…”
Section: Measurementsmentioning
confidence: 99%